Cerebral Angiographic Study of Anatomical Variations of Anterior Cerebral Artery Complex in Bangladeshi Population (Bangladesh Journal of Neuroscience, 2016)
Background: Anterior cerebral artery is an important terminal branch of internal carotid artery. It forms the anterior component of circle of Willis along with the anterior communicating artery. It is known for the frequent variations. The knowledge of anatomical variations in anterior cerebral artery is of considerable help to clinicians and interventionists. Method: Morphology and variations of the anterior cerebral arteries and the anterior communicating artery were studied in 90 patients undergone digital subtraction angiography (DSA).Results: Variations were found in 33% (n=30). Variations of the segments in relation with size, course, communications and terminations of the anterior cerebral artery (ACA) were noted. These were divided into different groups like hypoplasia, aplasia, duplication and fenestrations. Hypoplasia/Aplasia of proximal anterior cerebral artery (A1) was 24.5% in right side and 9% in left side. Anterior communicating artery (AComA) was found absent in 9% and fenestration in 9%. Callosomarginal artery was found absent in 2.2% in right side and 4.5% in left side. In right callosomarginal artery 6% had abnormal origin and 3.5% abnormal in left side.Pericallosal artery was present 100% on both sides. Conclusion: Variations of anterior cerebral artery complex anatomy is found common in Bangladeshi population.Bangladesh Journal of Neuroscience 2016; Vol. 32 (2): 56-62